Structure determination of SiO2 zeolite using electron diffraction - Tan, Selicia Yi En (Nanyang Technological University, 2025)
3D reconstruction provides a more complete structural understanding of a specimen, overcoming the limitations of conventional 2D electron diffraction patterns. Through tilting the specimen over a specified angular range with fixed increments, a tilt series of diffraction patterns at different tilt angles can be acquired. A 3D reconstruction of the reciprocal lattice can then be carried out using the tilt series, which provides more detailed structural information as compared to information obtained from individual 2D diffraction patterns. This study investigates the influence of tilt step size and specimen thickness on the quality of the 3D reconstruction. A smaller step size enables finer sampling of the reciprocal space, capturing more and finer details. Thicker specimens give rise to discrete diffraction spots due to a greater number of scattering planes. The fewer scattering planes in thinner specimens result in the formation of elongated reciprocal lattice points known as rel-rods due to incomplete destructive interference. This leads to increased streaking observed in the reconstruction of thinner specimens as compared to thicker specimens. Overall, finer step sizes and thicker specimens lead to more accurate and detailed reconstruction. The specimen used in this study is the SiO2 MFI zeolite. Simulations were performed using the abTEM code, TomViz and ParaView softwares for reconstruction. Due to current limitations of the abTEM code, the beam was tilted instead of the specimen. While this does not completely replicate the conventional specimen tilt, the effects of step size and specimen thickness on the quality of the reconstruction can still be studied.